Conversation-based AI for anxiety disorders might lower the threshold for traditional medical assistance: a case report - Grosshans, Martin; Paul, Torsten; Fischer, Sebastian Karl Maximilian; Lotzmann, Natalie; List, Hannah; Haag, Christina; Mutschler, Jochen (Frontiers in Public Health, 2024)
Artificial intelligence (AI) offers a wealth of opportunities for medicine, if we also bear in mind the risks associated with this technology. In recent years the potential future integration of AI with medicine has been the subject of much debate, although practical clinical experience of relevant cases is still largely absent. This case study examines a particular patient´s experience with different forms of care. Initially, the patient communicated with the conversation (chat) based AI (CAI) for self-treatment. However, over time she found herself increasingly drawn to a low-threshold internal company support system that is grounded in an existing, more traditional human-based care structure. This pattern of treatment may represent a useful addition to existing care structures, particularly for patients receptive to technology